The latest techniques for inducing macrophage differentiation - Lee, Kyungwoo; Choi, Yonghyun; Kim, Namju; Lee, Hee-Young; Choi, Jonghoon (Biotechnology and bioprocess engineering, 2024)
Macrophages play a prominent role in tissue development, homeostasis, and repair. In addition, their fundamental and well-known functions are integral to the host’s defense system, including immune responses and debris removal from apoptotic cells. These immune cells are remarkably responsive to various stimuli in the microenvironment, inducing multiple forms of differentiation with distinct phenotypes and roles. These stimuli comprise biochemical signals and physical biomaterial properties. Thus, understanding how immune cells differentiate is crucial for designing biomaterials, tissue scaffolds, implantable materials, and regenerative medicine, such as developing new drugs and immunomodulatory drug delivery systems. This review discusses about the latest techniques in inducing immune cell differentiation.